Effects of Inorganic Fertilizers on the Growth and Production Performance of Exotic Carps in Polyculture System
The present study was conducted to evaluate the effects of inorganic fertilizers in combination with constant supply of supplementary feeds on growth and production of exotic carps for a period of one year, from February 2007 to January 2008. Three treatments namely T1 Urea + TSP (2 : 1), 40 kg/ha, T2 Urea + TSP (2 : 1), 60 kg/ha and T3 (Urea + TSP (2 : 1), 80 kg/ha